About of Possibility of Existence of Zn(IV) Oxidation State in Heteroligand Complexes with Porphyrazine, trans-Di[benzo]porphyrazine, Phthalocyanine, and Oxo Ligands: Quantum-Chemical Review. Issue 3 (3rd May 2020) - Mikhailov, Oleg V.; Chachkov, Denis V.
ABSTRACT: Based on the quantum-chemical calculation using the Density Functional Theory (DFT) method, the existence possibility of zinc heteroligand complexes with porphyrazine and its analogs – trans -di[benzo]porphyrazine or phthalocyanine and oxo ligands with an oxidation state of IV which is unknown for this element, was shown. The data on the structural parameters and multiplicity of the ground state of these complexes were presented. Graphical Abstract: Comments on Inorganic Chemistry Volume ……., Issue ……., Pages ………. (2020). About of Possibility of Existence of Zn(IV) Oxidation State in Heteroligand Complexes with Porphyrazine, trans -Di[benzo]porphyrazine, Phthalocyanine and Oxo Ligands: Quantum-Chemical Review . Oleg V. Mikhailov, Denis V. Chachkov